2020
DOI: 10.3390/ijerph17103396
|View full text |Cite
|
Sign up to set email alerts
|

Trend in the Prevalence of Non-Daily Smoking and Their Relationship with Mental Health Using the Korea Health and Nutrition Examination Survey

Abstract: Introduction: Non-Daily Smoking (NDS), which is increasingly prevalent worldwide, has not yet attracted as much attention as has daily smoking in Asia. The aims of this study were to identify trends in the prevalence of NDS and to compare characteristics by age, gender, and mental health indicators such as depression, suicidality, and alcohol consumption in South Korea. Methods: We included 33,806 adults (aged ≥ 19 years) who participated in the Korean National Health and Nutrition Examination Survey (KNHNES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The adverse health effects of smoking have been extensively studied [ 16 ]. Numerous studies demonstrated that exposure to both first- and second-hand smoke can increase the risk of having a wide range of chronic physical and mental illnesses (e.g., [ 16 , 17 , 18 ]) and reduce life expectancy [ 19 ], which ultimately increases health care utilization and cost [ 16 , 20 ]. In addition, smoking has other behavioral and economic implications.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse health effects of smoking have been extensively studied [ 16 ]. Numerous studies demonstrated that exposure to both first- and second-hand smoke can increase the risk of having a wide range of chronic physical and mental illnesses (e.g., [ 16 , 17 , 18 ]) and reduce life expectancy [ 19 ], which ultimately increases health care utilization and cost [ 16 , 20 ]. In addition, smoking has other behavioral and economic implications.…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking status is associated with elevated suicide death risk; heavy smokers also exhibit greater than twice a risk than light smokers (Evins et al, 2017). Additionally, non-daily smoking and former smoking status are related to suicidal ideation and suicide plans and attempts (Kwan et al, 2020). Alcohol consumption is a well-known risk factor at the time of suicidal action and self-harm (Hurzeler et al, 2021; Larkin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…14 Although the prevalence rate of DS has recently declined in many countries, 15 previous studies have demonstrated an increasing trend in the number of non-daily smokers. 16,17 The results of a study in Mexico indicated that the prevalence of DS decreased by about 50% from 2002 to 2016, while the prevalence of NDS increased by 35% from 2009 to 2016. 18 In Iran as a developing country, few studies have examined the prevalence of NDS.…”
Section: Introductionmentioning
confidence: 99%